The effects of foam rolling applied to delayed-onset muscle soreness of the quadriceps femoris after Tabata training - Boguszewski Dariusz; Krawczyk Agata; Dębek Marlena; Adamczyk Jakub Grzegorz (Biomedical Human Kinetics)
The aim of the present study was to assess the effect of roll-over self-massage on the occurrence of symptoms of delayed post-workout muscle soreness after Tabata training.